Relation on phitoplankton community with Litopenaeus vannamei productivity in biocrete pond - Budiardi, T.; Widyaya, I.; Wahjuningrum, D. (Indonesian Society of Scientific Aquaculture (ISSA), 2007)
ABSTRACTManagement of phytoplankton is generally conducted by controlling the concentration of organic matter, fertilization and water exchange. Organic materials are from uneaten feed and excretion of shrimp. By using post facto method it was found four class of phytoplankton in biocrete pond at one cycle rearing of white shrimp (Litopenaeus vannamei). Population at early rearing period was dominated by Bacillariophyceae (50.4%; 13 species) and Cyanophyceae (42.41%; 1 species), followed by Dynophyceae (6.2%; 5 species) and Chlorophyceae (1.3%; 1 species). Increment in phytoplankton density was followed by increment in chlorophyll-a and oxygen from photosynthesis, and productivity was 2132 kg/pond.Keywords: phytoplankton, white shrimp, Litopenaeus vannamei, biocrete pond ABSTRAKPengelolaan fitoplankton umumnya dilakukan dengan mengoptimalkan bahan organik serta pemupukan dan pergantian air. Bahan organik berasal dari pakan buatan yang tidak terkonsumsi (sisa pakan) dan ekskresi dari udang. Dengan menggunakan metode post facto selama satu siklus pemeliharaan udang vaname (Litopenaeus vannamei) pada tambak biocrete diperoleh empat kelas fitoplankton. Dominasi Bacillariophyceae (50,4%; 13 jenis), Cyanophyceae (42,41%; 1 jenis) terjadi pada awal pemeliharaan yang diiukuti oleh Dynophyceae (6,2%; 5 jenis) dan Chlorophyceae (1,3%; 1 jenis). Peningkatan kelimpahan fitoplankton secara keseluruhan diikuti oleh peningkatan kandungan klorofil-a dan oksigen hasil fotosintesis total sehingga produktifitasnya mencapai 2132 kg/petakKata kunci: fitoplankton, udang vaname, Litopenaeus vannamei, tambak biocrete